Mapeamento genético no camarão marinho Litopenaeus Vannamei (Crustacea, Decapoda) - Gonçalves, Michelle Mantovani (2009)
Two genetic linkage maps were constructed referent to two full-sib families (G1 and G2) of the marine shrimp species Litopenaeus vannamei, and the integration of these maps was accomplished. The mapping was based on polymorphic markers derived from nine AFLP (Amplified Fragment Length Polymorphism) primers. A total of 103 and 59 segregating polymorphic markers were used in the construction of the maps for families G1 and G2, respectively. The G1 family map consisted of 14 linkage groups, with estimated genome coverage of approximately 350 cM. The G2 map presented 4 linkage groups, with genome coverage of around 300 cM. The integration of the maps evidenced eight AFLP anchor markers in a same linkage group (LG1) in both families, to which 66 markers were allocated, leading to a well saturated linkage group, with estimated genome coverage of 874.16 cM.